STUDYING HISTORY IN EDUCATION: MODERN PEDAGOGICAL METHODS AND INNOVATIVE TECHNOLOGIES - Kadirova Dildora Sabirdjanovna (Sciental Journals Publishing, 2025)
This article explores the effectiveness of applying modern pedagogical methods and innovative technologies in teaching history. In the study, along with traditional methods of teaching history, the influence of the use of multimedia, virtual excursions, artificial intelligence, and other interactive technologies on the educational process was analyzed. The research results show a significant increase in students' interest, level of knowledge, and ability to think critically using innovative technologies. The necessity of assisting teachers in applying effective pedagogical methods and introducing modern methods to make learning interesting and effective for students was emphasized. The results of the study include recommendations aimed at modernizing the education system of Uzbekistan and adapting it to global educational standards.
Keywords: Historical education, modern pedagogical methods, innovative technologies, multimedia, artificial intelligence, interactive methods, teaching effectiveness, digitalization in education, the education system of Uzbekistan, critical thinking, student motivation.